The global march against child labour-Philippines: A case study - Trew, John B. (Animo Repository, 2001)
A major social problem affecting the Philippine archipelago is the abuse of child rights associated with child labor. The plight of children throughout the country serves to fuel the fire of child advocacy movements. The thesis entitled, The Global March Against Child Labour Philippines: A Case Study, will examine the notions of child advocacy as it pertains to the legal and social outlets of change. The thesis is divided into three components. Chapter 1 examines the issues addressed by the research proposal. These include the objectives of the study, the scope and limitations including the justification of the case study, the significance of the research and advocacy avenues associated with the Global March. Chapter II probes the literature in the field of child rights and advocacy. The chapter also places the study in context to the literature review and the reasons behind its contributions to the field. Chapter III explores the policy environment surrounding the protection of children. The legal framework serves as the basis for child advocacy movements more often than not understanding this framework is vital towards achieving a comprehensive analysis of the issues associated with child advocacy. Chapter IV yields an analysis of the theoretical framework of child advocacy. Areas under examination include the notion of child participation, definition of terms encompassing the role of child advocacy as a distinct component of public policy, and the role the methodology plays as a tool for evaluating the impact of the case study. Chapter V outlines the evolutionary developments associated with the Global March Philippines. Analysis of the Global March International, the coordinating organization for the Global March Philippines, the goals of the campaign, and those actors the case study seeks to influence are all delineated as significant contributions to the movement.